Primary Yolk Sac Tumor of the Liver: A Rare Cause of Bile Duct Obstruction - Sahil M. Patel; Kenneth M. Sigman; Mohannad F. Dugum (Case Reports in Gastrointestinal Medicine)
Primary yolk sac tumor (YST) of the liver is an extremely rare extragonadal germ cell tumor. Here, we present a case of a young man who developed primary YST of the liver which metastasized to periductal lymph nodes causing bile duct obstruction. A 32-year-old male was referred from an outside hospital for evaluation of painless jaundice. Initial investigation showed common bile duct compression from periductal lymph nodes. Inital biopsy results were concerning for adenocarcinoma. The patient was ultimately diganosed with primary YST of the liver. He was then started on a curative-intent chemotherapy regimen of bleomycin, etoposide, and cisplatin. This case highlights the importance of keeping the primary YST of the liver on the differential diagnosis as initial staining patterns are similar to adenocarcinoma which has a very different management.